Rural Income Generating Activities : A Cross Country Comparison - Davis, Benjamin; Winters, Paul; Carletto, Gero; Covarrubias, Katia; Quinones, Esteban; Zezza, Alberto; Stamoulis, Kostas; Bonomi, Genny; DiGiuseppe, Stefania (Washington, DC: World Bank, 2012)
Cross country comparisons of rural income generating activities are analyzed to identify ways to design more effective and better targeted rural development policies. The full range of rural income generating activities carried out by rural households are examined, including: 1) the relative importance of the gamut of income generating activities in general and across wealth categories, both at the level of the rural economy and the rural household; 2), the relative importance of diversification versus specialization in rural income generation; 3) the relationship between key household assets and the participation in and income earned from these activities; and 4) the influence of rural income generating activities on poverty and inequality. For most countries the largest share of income stems from off farm activities, and the largest share of households have diversified sources of income. Diversification, not specialization, is the norm, although most countries show significant levels of household specialization in non-agricultural activities as well.